PENERAPAN HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL (HIRARC) SEBAGAI PENGENDALIAN POTENSI KECELAKAAN KERJA DI BAGIAN PRODUKSI BODY BUS PT. X MAGELANG - Annisa Devi Primasari; Hanifa Maher Denny; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Hazard Identification Risk Assessment and Risk Control (HIRARC) is a tool or a method to identify, assess or measure and control hazards based activities work in every workplace. PT. X Magelang doesn’t have HIRARC method so that the company is also hasn’t apply SMK3. The aim of this research was to describe the identified of potential hazards, the risk assessment and control (HIRARC). The study utilized qualitative approach using interview and field observation. The subjects of this research were five informants and the production of the body bus, while triangulation informants are the manager of body bus area and the staff of SHE. The finding of this research was able to identify some potential hazards such as minor injuries, scratches, slips and trips, falls, burns, back/neck, RSI (Repetitive Strain Injury), cuts, hearing loss, toppling incidents, inhalations. While the potential of risks belonged to extreme 9,2% high 44,6% medium 21,5% and low 24,6%.